Climate change impact on thunderstorms: Analysis of thunderstorm indices using high-resolution regional climate simulations - Lukas Schefczyk; Günther Heinemann (Meteorologische Zeitschrift, 2017)
It is generally assumed that the temperature increase associated with global climate change will lead to increased thunderstorm intensity and associated heavy precipitation events. In the present study it is investigated whether the frequency of thunderstorm occurrences will in- or decrease and how the spatial distribution will change for the A1B scenario. The region of interest is Central Europe with a special focus on the Saar-Lor-Lux region (Saarland, Lorraine, Luxembourg) and Rhineland-Palatinate.Daily model data of the COSMO-CLM with a horizontal resolution of 4.5 km is used. The simulations were carried out for two different time slices: 1971–2000 (C20), and 2071–2100 (A1B). Thunderstorm indices are applied to detect thunderstorm-prone conditions and differences in their frequency of occurrence in the two thirty years timespans. The indices used are CAPE (Convective Available Potential Energy), SLI (Surface Lifted Index), and TSP (Thunderstorm Severity Potential).The investigation of the present and future thunderstorm conducive conditions show a significant increase of non-thunderstorm conditions. The regional averaged thunderstorm frequencies will decrease in general, but only in the Alps a potential increase in thunderstorm occurrences and intensity is found. The comparison between time slices of 10 and 30 years length show that the number of gridpoints with significant signals increases only slightly. In order to get a robust signal for severe thunderstorm, an extension to more than 75 years would be necessary.